Foreign languages and their impact on unemployment - Donado Gomez, Alejandro (Labour, 2017)
Using a large European data set, I investigate the impact of knowing foreign languages on unemployment for the first time. The focus is on natives (not on immigrants). I find that (1) knowing a foreign language reduces the probability of being unemployed by at least 3.4 percentage points; (2) females benefit more than males from learning foreign languages; (3) English and German tend to have a larger and more robust impact on unemployment than French, Spanish, and Italian; (4) but the impact of all these five languages varies considerably across countries.